2008
DOI: 10.1177/0267658307082980
|View full text |Cite
|
Sign up to set email alerts
|

Development of the ability to lexically encode novel second language phonemic contrasts

Abstract: International audienceSecond language (L2) learners must often learn to perceive and produce novel L2 phoneme contrasts. Although both research and intuition suggest that these difficulties can be overcome to some extent with exposure to the L2, it is not known what consequences this kind of learning has for the phonological structure of the L2 lexicon. We present an experiment designed to investigate the lexical representations that learners establish for L2 words that contain novel phonemic contrasts. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 31 publications
(53 reference statements)
3
62
1
Order By: Relevance
“…This is in striking contrast with most of the studies reviewed in the first paragraphs of this introduction, namely Curtin et al (1998), Pallier et al (2001) and Hayes-Harb and Masuda (2008), all of which provide evidence that is consistent with homophonous lexical entries for L2. The present study aims to answer the question of how L2 learners can establish contrastive lexical representations for phonemes that they do not reliably discriminate in listening tasks.…”
Section: Introductioncontrasting
confidence: 91%
“…This is in striking contrast with most of the studies reviewed in the first paragraphs of this introduction, namely Curtin et al (1998), Pallier et al (2001) and Hayes-Harb and Masuda (2008), all of which provide evidence that is consistent with homophonous lexical entries for L2. The present study aims to answer the question of how L2 learners can establish contrastive lexical representations for phonemes that they do not reliably discriminate in listening tasks.…”
Section: Introductioncontrasting
confidence: 91%
“…This learner result suggests continuity between prelexical non-native perception and L3 word recognition. Many previous studies (Pallier et al, 2001, Cutler & Otake, 2004, Weber & Cutler, 2004, Broersma 2005, Cutler and Broersma, 2005, Cutler et al, 2006, Broersma & Cutler, 2008, Escudero et al, 2008, Hayes-Harb & Masuda 2008 have already shown that L2 words containing contrasts which are difficult for learners to perceive pose problems in word recognition. The present study shows that this continuity can also be found in L3 word recognition.…”
Section: Discussionmentioning
confidence: 96%
“…Remarkably, L2 learners’ knowledge of frequent phonological patterns was used to bootstrap perception even at Test 1. These results suggest that prior to testing (i.e., during the first year of classroom learning), L2 learners began encoding statistical and phonological information in L2 representations (e.g., Hayes‐Harb, ; Hayes‐Harb & Masuda, ).…”
Section: Discussionmentioning
confidence: 97%